SOSIALISASI PENYELAMATAN PENYU ACEH DI PANTAI SUAK GEUDUBANG ACEH BARAT - Neneng Marlian; Nabil Zurba; Fitria Rahmayanti (Universitas Teuku Umar, 2021)
Turtles are marine reptiles that have lived hundreds of millions years ago, where as the six species turtles from the seven species turtles, that exist in the world today are found in Indonesia. However, the continuous hunting and catching of turtles by humans is impacted to the threat turtle species in the world, including the Aceh’s turtles of Indonesian. The implementation on this activity was a service to the community, which purpused to increasing public awareness in order to protected and preserved the Aceh’s turtles. This community service activity was conducted on October 27 in 2020 at Suak Geudubang Beach, Sama Tiga Sub-district, West Aceh Regency. Socialization targeting was the coastal community who lived around in the Suak Geudubang Beach of Sama Tiga. The method of service implementation was trough a lecturing approach and opening discussion. The Aceh’s turtles socialization activity provided an explanation of, definitioned, distributioned of turtles habitat, ecologically and economically potential, international conventioned and Indonesian stated laws that conserved the protecting of turtles, th efforted of conservation Aceh’s turtles, the potential coast of Aceh as locationed for Aceh's turtles, community empowerment as the main actor and spearhead in the efforted of conservation Aceh's turtles. Socialization rescued of Aceh’s turtles has played a role in increasing public awareness sustainability in Aceh, especially on the Suak Geubang Beach, West Aceh.